Electrodeposition and corrosion behaviour of nanocrystalline Fe–P coatings. (4th March 2019) - Kovalska, N.; Hansal, W.E.G.; Tsyntsaru, N.; Cesiulis, H.; Gebert, A.; Kautek, W.
ABSTRACT: Electrodeposition of alloy coatings is a proven route to corrosion protection of metal substrates but has met some restrictions due to changed European regulations. Iron-phosphorus codeposits appear to be eco-friendly candidates for substitution of hard chromium, and alloys such as Ni–P, Co–Ni etc. The main task in formulating proper electrolytes for Fe–P deposition is the stabilisation of the Fe 2+ ion to hinder the oxidation to Fe 3+ by air. In this work glycine was selected as complexing agent for Fe 2+ . Fe–P layers were deposited from a glycine-containing electrolyte at various glycine concentrations, current densities and temperatures. The properties of the layers vary greatly with a change of each applied parameter. Interaction of complex equilibria and pH change due to cathodic hydrogen evolution can lead to electrochemical oscillations which result in multilayer structures of the deposits. The corrosion resistance of Fe–P layers obtained in this work is comparable to industrially used Ni–P coatings.